2014
DOI: 10.1007/s10853-014-8373-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated cellulose in wood coatings: mechanical properties of free composite films

Abstract: Composite films of nanofibrillated cellulose (NFC), derived from beech wood pulp, and 8 commercial acrylic and alkyd polymeric binders were prepared. Structural and mechanical properties of the composites were assessed by microscopy and tensile tests before and after aging. While the NFC was compatible with acrylate polymers, it formed undesired aggregates during processing with the alkyd polymers. Modulus of elasticity, tensile strength, and elongation at break of prepared films depended on the initial proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 35 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…Similarly, but to a lesser extent, strength and stiffness also increased with 2% CNC, while extensibility of these films was largely preserved. This overall trend, i.e., increased strength and stiffness with simultaneously reduced extensibility, agrees well with reports in the literature on CNFreinforced coatings (Grüneberger et al 2014a) and is also valid for inorganic platelet-reinforced coatings (Nikolic et al 2015). For CNF, such an effect is proposed to be due to well-known percolation phenomena, which are correlated with the length and content of nanocellulosic filler in polymers (Azizi Samir et al 2005;Bulota et al 2012;Littunen et al 2013;Xu et al 2013).…”
Section: Mechanics Of Free-standing Coating Filmssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, but to a lesser extent, strength and stiffness also increased with 2% CNC, while extensibility of these films was largely preserved. This overall trend, i.e., increased strength and stiffness with simultaneously reduced extensibility, agrees well with reports in the literature on CNFreinforced coatings (Grüneberger et al 2014a) and is also valid for inorganic platelet-reinforced coatings (Nikolic et al 2015). For CNF, such an effect is proposed to be due to well-known percolation phenomena, which are correlated with the length and content of nanocellulosic filler in polymers (Azizi Samir et al 2005;Bulota et al 2012;Littunen et al 2013;Xu et al 2013).…”
Section: Mechanics Of Free-standing Coating Filmssupporting
confidence: 89%
“…Generally, straightforward dispersion of CNC in waterborne formulations is reported, whereas chemical hydrophobization, for example by means of an organofunctional silane (Landry and Blanchet 2011) or acryloyl chloride or alkyl quaternary ammonium bromides , was required for nonpolar systems. Addition of CNF to coatings also provided improvements in mechanics (Grüneberger et al 2014a;Veigel et al 2014) and exhibited beneficial effects on the dispersion of inorganic additives (Grüneberger et al 2015;Jämsä et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing effect of three types of NFC (mechanically prepared NFC, TEMPO-oxidized, and enzymatically pretreatment NFC) as a filler material in polysodium acrylate superabsorbents was studied; it was found that NFC and enzymatically isolated NFC were more effective than TEMPO NFC as a filler material [11]. NFC also showed reinforcing effect when mixed with different types of acrylates for wood coating before and after aging [12,13]. NFC was graftcopolymerized with acrylic monomers (glycidyl methacrylate, ethyl acrylate, methyl methacrylate, butyl acrylate, and 2-hydroxyethyl methacrylate) to impart its hydrophobic character and improve its heat resistance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the UV protection efficiency of these combined products consisting of inorganic UV absorbers (ZnO, TiO2, CeO2) and a transparent coating such as water-based acrylic systems or maleic anhydride modified polypropylene or polyurethane were reported in several studies (9, 10,11,12,13). An addition of nano-fibrillated cellulose for carrying and homogenously distributing of UV absorbers for wood coatings was reported by Grüneberger et al (14,15). However, the UV radiation causes a self-degradation of the applied polymer coatings, which affects the long-term performance of such systems.…”
Section: Introductionmentioning
confidence: 99%